2019
DOI: 10.1002/anie.201907880
|View full text |Cite
|
Sign up to set email alerts
|

Design Parameters of Tissue‐Engineering Scaffolds at the Atomic Scale

Abstract: Stem‐cell behavior is regulated by the material properties of the surrounding extracellular matrix, which has important implications for the design of tissue‐engineering scaffolds. However, our understanding of the material properties of stem‐cell scaffolds is limited to nanoscopic‐to‐macroscopic length scales. Herein, a solid‐state NMR approach is presented that provides atomic‐scale information on complex stem‐cell substrates at near physiological conditions and at natural isotope abundance. Using self‐assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…To understand the mechanism of gelation, the macroscale morphology of fibrillar network, and the underlying molecular structure of fibrils, Nagy‐Smith and co‐workers utilize solid‐state NMR to develop a full structural model for MAX1 fibrils and characterize molecular conformation, β‐sheet organization, and intersheet interactions on all levels of structure (Figure 1D–G). [ 28 ] To control stem‐cell behaviors beyond nanoscopic‐to‐macroscopic length scales, Jekhmane and colleagues provide atomic‐scale design strategies and related parameters of self‐assembled peptide scaffold by solid‐state NMR approach, [ 29 ] such as scaffold‐assembly degree, soft or stiff mechanics, well‐defined homogeneity, which reveals a highly ordered nanofibrillar structure at the atomic scale and permit to improve peptide design parameters for favorable stem‐cell scaffolds in implantable cell constructs (Figure 1H–J). Since designer self‐assembling peptides have very consistent sequence characteristics involved in charge and hydrophobicity on the peptide backbone, molecular self‐assembly‐mediated hydrogelation process is better understood compared to other polymer systems, [ 20 ] such as lipid, polysaccharide, and other chemical polymer.…”
Section: Molecular Self‐assembly In Designer Peptides and Current Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the mechanism of gelation, the macroscale morphology of fibrillar network, and the underlying molecular structure of fibrils, Nagy‐Smith and co‐workers utilize solid‐state NMR to develop a full structural model for MAX1 fibrils and characterize molecular conformation, β‐sheet organization, and intersheet interactions on all levels of structure (Figure 1D–G). [ 28 ] To control stem‐cell behaviors beyond nanoscopic‐to‐macroscopic length scales, Jekhmane and colleagues provide atomic‐scale design strategies and related parameters of self‐assembled peptide scaffold by solid‐state NMR approach, [ 29 ] such as scaffold‐assembly degree, soft or stiff mechanics, well‐defined homogeneity, which reveals a highly ordered nanofibrillar structure at the atomic scale and permit to improve peptide design parameters for favorable stem‐cell scaffolds in implantable cell constructs (Figure 1H–J). Since designer self‐assembling peptides have very consistent sequence characteristics involved in charge and hydrophobicity on the peptide backbone, molecular self‐assembly‐mediated hydrogelation process is better understood compared to other polymer systems, [ 20 ] such as lipid, polysaccharide, and other chemical polymer.…”
Section: Molecular Self‐assembly In Designer Peptides and Current Statusmentioning
confidence: 99%
“…[ 24,31 ] Concurrently, molecular self‐assemblies in peptides and proteins are moving from modulating cellular functionality in 3D context to the predictive creation of new biomimetic nanomaterials by bioengineering strategies at the molecular or atomic levels. [ 29,32 ] All in all, based on bottom‐up bioengineering strategies the predictive design and biomimetic capacity of designer self‐assembling peptide hydrogels would enhance the development of more physiological and reliable 3D cell models and help the biomedical industry to develop better molecular or cellular therapy approaches in tissue engineering, regenerative medicine, cancer management, or other biomedical applications.…”
Section: Molecular Self‐assembly In Designer Peptides and Current Statusmentioning
confidence: 99%
“…Since biotin—composed of ureido and tetrahydrothiophene rings sideways fused and by a valeryl chain—proved to facilitate and stabilize self-assembling peptide nanofibers (SAPs) [ 17 , 18 , 19 ] without altering their biocompatibility, we added to the T13 peptide an N-terminal biotinylated oligoglycine tag to foster its self-assembly propensity, and to enhance its biomechanical properties ( Figure S2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as experimentally observed, the authors pointed out that biotin significantly supports the hierarchical self-assembly into ordered β-sheet structures and improves the biomechanics of the final scaffolds [ 17 , 18 ]. Jekhmane et al also reported that by using solid state NMR, that biotinylated scaffolds assembly degree, mechanics, and homogeneity correlate with favorable neural stem cell behavior [ 19 ]. In another effort, Davis et al designed biotinylated peptide nanofibers for the prolonged delivery of insulin-like growth factor 1 (IGF-1) for improving cell therapy for myocardial infarction [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels have a unique combination similar to natural ECM and are attractive biomaterials for the osteochondral tissue engineering. The hydrogel microenvironment can be strictly controlled through the adjustment of many biophysical and biochemical properties, such as the matrix mechanics, degradability, microstructure, cell adhesion, and cell-cell interactions (Brown and Anseth, 2017;Jekhmane et al, 2019). These properties can be easily manipulated to suit for a variety of biomedical applications (Sun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%